The simultaneous presence of three different Newcastle Disease Virus Genotypes in various bird species in a public bird garden - Soltani, M; Shoushtari, AH; Molouki, A; Babaeimarzangou, SS; Abdoshah, M; Bashashati, M; Fallah Mehrabadi, MH (Journal of the Hellenic Veterinary Medical Society, 2024)
Newcastle disease (ND) is one of the most important contagious bird diseases. Not only it continuously causes significant economic damage to the commercial poultry industry, but also it is of clinical importance as it occurs in a wide range of free-living and captive birds. Although different types of commercial vaccines are extensively used, the disease has not been eradicated. Between October 2018 and March 2019, three different outbreaks of ND were observed in three different captive bird species of pigeons, peafowls, and pheasants at the Saei public bird garden in Tehran. Genetic identification of viral isolates of AMMM116 (pheasant), AMMM122 (peafowl), and AMMM160 (pigeon) indicated the presence of genotypes VII.1.1, II, and VI.2.1.2, respectively. The virus isolated from the pheasants was closely related to the VII.1.1 subgenotypes obtained from commercial poultry farms in different parts of Iran. Moreover, the VI.2.1.2 isolate obtained from the ND outbreak in pigeons was related to the isolates obtained from pigeons in Nigeria and Kenya. Lastly, we isolated a genotype II NDV, identical to the common vaccine strains, from immature peacocks that had an acute death. The peacocks were not vaccinated, therefore, we speculated that the presence of genotype II could be because of the spillover of vaccine strains from commercial poultry flocks to wild birds that had visited the park and landed in the roofless aviary. The results of this study indicate the simultaneous circulation of different NDV genotypes in a small geographic location and emphasize the importance of imposing more restricted biosecurity measures.